Spatial Analysis of Limboto Lake - Jefri D Ladja; Faizal Kasim; Miftahul Khair Kadim (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
Remote sensing satellite imagery data can be used to monitor the condition of the lake, especially the lake area at certain times, especially the extent of Lake Limboto. The purpose of this research is to know the area of Limboto Lake using Landsat-OLI 2015 satellite image data. The research method used is image data processing which includes image cutting, image reinforcement, RGB color composite (R = NIR + SWIR, G = NIR, B = NIR-Red), and the image classification is done by digitizing directly on the screen (on screening digitizing) by considering the presence of water vegetation. Furthermore, data analysis is done by calculating the extent of Lake Limboto on the image of classification results. The results showed that the area of Lake Limboto in 2015 was 2,943 hectares. Keywords: spatial analysis; lake; Limboto Lake.